Development of multiplex pcr platform for simultaneous detection of selected foodborne pathogens / Thenmoly Utayakumaran - Thenmoly , Utayakumaran (2019)
Foodborne outbreaks are threatening human population worldwide especially in Malaysia where the occurrence of food poisoning is becoming more prevalent due to contamination caused during food production, food preparation and handling. Most outbreaks are commonly caused by E. coli, Salmonella sp., Listeria sp., Shigella spp., Staphylococcus aureus and Yersinia enterocolitica. Thus, a cost-effective, rapid and sensitive assay is required to find the cause of contamination before such contaminated foods disseminated widely in the market. In this study, a multiplex PCR assay was developed to allow simultaneous detection of six foodborne pathogens. The assay targets species-specific regions namely phoA, hilA, hyl, ipaH, rpoB and yst respective to E. coli, Salmonella sp., Listeria sp., Shigella spp., Staphylococcus aureus and Yersinia enterocolitica. The specificity and detection limit of the assay was evaluated by using 80 known bacterial cultures and 5 spiked food samples. The primers designed were highly specific except the mphoA primer pair as it is cross-reacted with E,coli and Shigella strains. Whereas, the detection limit for simultaneous detection of all targeted pathogens was up to 104 CFU/ml even though limit of up to 101 CFU/ml for E. coli, Listeria and Shigella; 102 CFU/ml for Salmonella and Yersinia was obtained respectively. When tested with spiked food samples the detection limit of E. coli was 101 CFU/ml; Salmonella, Listeria and Shigella was 102 CFU/ml in spite the simultaneous detection limit of all the six pathogens was 106 CFU/ml. In short, the developed multiplex PCR assay allows rapid and cost-effective simultaneous detection of the six common foodborne pathogens.